2020
DOI: 10.1111/mec.15569
|View full text |Cite
|
Sign up to set email alerts
|

A layover in Europe: Reconstructing the invasion route of asexual lineages of a New Zealand snail to North America

Abstract: Non‐native invasive species are threatening ecosystems and biodiversity worldwide. High genetic variation is thought to be a critical factor for invasion success. Accordingly, the global invasion of a few clonal lineages of the gastropod Potamopyrgus antipodarum is thus both puzzling and has the potential to help illuminate why some invasions succeed while others fail. Here, we used SNP markers and a geographically broad sampling scheme (N = 1617) including native New Zealand populations and invasive North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 69 publications
0
24
0
Order By: Relevance
“…In other systems, it has been shown that invaders have lower microbial diversity and/or a subset of microbes relative to that present in native populations (Minard et al, 2015;Zepeda-Paulo et al, 2018). Invasive P. antipodarum populations feature low genotypic diversity relative to the native range (Donne et al, 2020;Dybdahl & Drown, 2011;Verhaegen et al, 2018) and mitochondrial haplotypes of invaders represent genetic subsets of native mitochondrial haplotype diversity (Städler et al, 2005). However, this genetic subsampling in inva- microbiome down to specialized taxa (Foster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In other systems, it has been shown that invaders have lower microbial diversity and/or a subset of microbes relative to that present in native populations (Minard et al, 2015;Zepeda-Paulo et al, 2018). Invasive P. antipodarum populations feature low genotypic diversity relative to the native range (Donne et al, 2020;Dybdahl & Drown, 2011;Verhaegen et al, 2018) and mitochondrial haplotypes of invaders represent genetic subsets of native mitochondrial haplotype diversity (Städler et al, 2005). However, this genetic subsampling in inva- microbiome down to specialized taxa (Foster et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Hood, pers comm. ), Pennsylvania (R. Morgan, pers comm., Levri et al 2020), While asexual NZMS harbor a great deal of genetic diversity (Jokela et al 2003), only a handful of NZMS clones have been successful invaders (Städler et al 2005, Alonso and Castro-Díez 2012, Donne et al 2020).…”
Section: New Zealand Mud Snail Invasionmentioning
confidence: 99%
“…As these alterations continue, predicting outcomes, mitigating damages, and restoring the native environment and community will become increasingly difficult. Because the western US1 population has existed at least since 1987 (Bowler 1991), the invasion in Pennsylvania is likely a secondary invasion originating via human-mediated transport of individuals from the western US (also see Donne et al . 2020).…”
Section: New Zealand Mud Snail Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…We here describe important steps forward in identifying an effective anesthesia technique for Potamopyrgus antipodarum, a New Zealand freshwater snail model system that is a prominent model system for the evolution of sexual reproduction (e.g., Neiman et al 2011), ecotoxicology (e.g., Geiß et al 2017), invasion biology (e.g., Donne et al 2020), and host-parasite interactions (e.g., Bankers et al 2017). Studies of P. antipodarum often incorporate tissue manipulation (e.g., tentacle severing as a test of tissue regeneration; Krois et al 2013) or require determination of male vs. female status (e.g., Jalinsky et al 2020).…”
mentioning
confidence: 99%